Hubungan Ganguan Akibat Kekurangan Yodium (GAKY) dengan Prestasi Belajar di SDN Tanggalrejo Kecamatan Mojoagung Kabupaten Jombang - Pitaloka, Diah Ayu; Ratnawati, Mamik; Ulfa, Ida Nikmatul (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2017)
The Correlation OfÂ  Iodine Deficiency DisorderÂ  (IDD) WithÂ  Learning AchievementÂ  At Public Ementary School ( SdnÂ  ) Tanggalrejo Village ,Â  MojoagungÂ  Sud District , In Jombang District. One nutritional problem In indonesia is IDD.Â  IDD is known toÂ  be able to effectÂ  abnormality such as mumps, cretin, intelligence disorder,Â  mental disorderÂ  and physical development disorder that affectÂ  the quality of HR (Human Resources). Impaired intelegence of child, make the child will have difficulty to achieveÂ  learning. The research aimedÂ  to understandÂ  the correlation of IDD withÂ  learningÂ  achievementÂ  atÂ  ( SDN )Â  TanggalrejoÂ  Village, Mojoagung Sub district inÂ  Jombang District. This researchÂ  wasÂ  an analytic correlation with cross sectional approach. TheÂ  population as much as 54 respondent wasÂ  theÂ Â  students ofÂ Â  grade 3Â  at Public Elementary school ( SDNÂ  ) TanggalrejoÂ  Village Mojoagung sub district inÂ  JombangÂ  District , and total ofÂ  samples wasÂ Â  54 respondentsÂ  with theÂ  technique of samplingÂ  usedÂ  total sampling. The independent variableÂ  wasÂ  IodineÂ  deficiencyÂ  Disorders(IDD) and the dependent variableÂ  was learning achievement with the instrument in the form of inspection and palpation ofÂ  thyroid gland and documentation of the valueÂ  withÂ Â  Spearman rank test. The results showed that the mostÂ  (70.4%) IDD wasÂ  0 degreesÂ  and the mostÂ  (33.3%) learning achievement was less , itÂ  was obtainedÂ  r valueÂ  = 0.351, Ï = 0.009 and É‘ = 0.05, because Ï <É‘ then HoÂ  wasÂ  refusedÂ  it meantÂ  thereÂ  wasÂ  correlationÂ  of IDD with grade 3Â  student â€˜s achievementÂ  atÂ Â Â  Public Elementary SchoolÂ  (SDN ) TanggalrejoÂ  Village , Mojoagung Sub district inÂ  Jombang District.Based on the description above, so that the increase ofÂ  iodized salt consumption is needed byÂ  school-age children to prevent the emergence of new problems, and as a correction for peopleÂ  withÂ  IDD. And necessary counceling about the important iodized salt to community.Â Keywords: IDD, Learning Achievement